Youth and the Crisis Unemployment, Education and Health in Europe - Coppola, Gianluigi; O'Higgins, Niall (2015)
The recent recession has led to an ongoing crisis in the youth labour market in Europe. This timely book deals with a number of areas related to the context, choices and experiences of young people, the consequences of which resonate throughout their lives.